Practical Guidance for Teachers: Overview of Student at Risk Behaviour - Prijonggo, Constantinus Wahju; Agnes Maria Sumargi (Faculty of Psychology, Universitas Surabaya, 2002)
The behaviours of student at risk, such as truancy, vandalism, drug abuse, disruptive behaviour and antisocial behaviour, have been a major concern for teachers. As teachers, we may find it hard to manage students with these behaviours. Our behaviour management strategies do not seem to work effectively with these students. The problem behaviours continue to occur and even increase in frequency. In fact, students at risk, particularly adolescents at risk, have utilised our behaviour management strategies to attract the attention of fellow students (Houghton & Caroll, 1996). This article outlines how the students at risk behaviour utilise behaviour man- agement, why they do it, and how to deal with this problem. Perilaku siswa berisiko, seperti membolos, vandalisme, penyalahgunaan obat, perilaku mengganggu dan antisosial, merupakan masalah besar bagi guru. Sebagai guru, kita mengalami kesulitan mengatasi masalah tersebut. Strategi manajemen perilaku kita rasanya tak berjalan efektif pada siswa-siswa demikian. Perilaku bermasalah demikian itu terus terjadi bahkan meningkat frekuensinya. Nyatanya, siswa berisiko terutama para remaja, memanfaatkan strategi manajemen perilaku kita justru untuk menarik perhatian teman-temannya (Houghton & Caroll, 1996). Artikel ini memaparkan bagaimana para siswa berisiko tersebut memanfaatkan manajemen perilaku, mengapa mereka melakukan itu, dan bagaimana menghadapi masalah ini.